2022
DOI: 10.2196/40022
|View full text |Cite
|
Sign up to set email alerts
|

Posttraining Outcomes, Acceptability, and Technology-Based Delivery of the STAC Bystander Bullying Intervention Teacher Module: Mixed Methods Study

Abstract: Background Bullying is a significant problem for youth associated with wide-ranging negative consequences. Providing students who witness bullying with intervention strategies to act as defenders can reduce bullying and negative associated outcomes for both targets and bystanders. Educating teachers about bullying and training them to support students to intervene as defenders may increase the efficacy of bystander programs as teachers’ attitudes and responses to bullying relate to bystander behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…The STAC Parent Module can be included as part of the current STAC intervention, which is a relatively low-cost program compared to comprehensive, school-wide bullying prevention programs. Next, although research suggests that school personnel in rural middle schools believe that parents need to be involved in bullying prevention (Midgett et al, 2021; Midgett et al, 2022), parent involvement in bullying prevention has been identified as an obstacle for rural schools (Leadbeater et al, 2013). Findings from this study indicate that program flexibility may remove barriers to implementation related to time constraints experienced by parents in rural communities such as providing access the training through a smartphone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The STAC Parent Module can be included as part of the current STAC intervention, which is a relatively low-cost program compared to comprehensive, school-wide bullying prevention programs. Next, although research suggests that school personnel in rural middle schools believe that parents need to be involved in bullying prevention (Midgett et al, 2021; Midgett et al, 2022), parent involvement in bullying prevention has been identified as an obstacle for rural schools (Leadbeater et al, 2013). Findings from this study indicate that program flexibility may remove barriers to implementation related to time constraints experienced by parents in rural communities such as providing access the training through a smartphone.…”
Section: Resultsmentioning
confidence: 99%
“…The intention to use Parent STAC strategies was measured using an adapted version of the Use of STAC Strategies for students (Midgett, Doumas, et al, 2017) and teachers (Midgett et al, 2022). The items were adapted for parents by replacing “student” with “adolescents.” The four-item measure asks parents “How likely are you to use these strategies to support your adolescent to intervene in bullying in the future?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations